Bosutinib in Resistant and Intolerant Pediatric Patients With Chronic Phase Chronic Myeloid Leukemia: Results From the Phase I Part of Study ITCC054/COG AAML1921. - Brivio, Erica; Pennesi, Edoardo; Willemse, Marieke E.; Huitema, Alwin D.R.; Jiang, Yilin; Van Tinteren, Harm D.R.; Van Der Velden, Vincent H.J.; Beverloo, Berna H.; Den Boer, Monique L.; Rammeloo, Lukas A.J.; Hudson, Chad; Heerema, Nyla; et al. (Journal of Clinical Oncology, 2024)
PURPOSE: Bosutinib is approved for adults with chronic myeloid leukemia (CML): 400 mg once daily in newly diagnosed (ND); 500 mg once daily in resistant/intolerant (R/I) patients. Bosutinib has a different tolerability profile than other tyrosine kinase inhibitors (TKIs) and potentially less impact on growth (preclinical data). The primary objective of this first-in-child trial was to determine the recommended phase II dose (RP2D) for pediatric R/I and ND patients. PATIENTS AND METHODS: In the phase I part of this international, open-label trial (ClinicalTrials.gov identifier: NCT04258943), children age 1-18 years with R/I (per European LeukemiaNet 2013) Ph+ CML were enrolled using a 6 + 4 design, testing 300, 350, and 400 mg/m2 once daily with food. The RP2D was the dose resulting in 0/6 or 1/10 dose-limiting toxicities (DLTs) during the first cycle and achieving adult target AUC levels for the respective indication. As ND participants were only enrolled in phase II, the ND RP2D was selected based on data from R/I patients. RESULTS: Thirty patients were enrolled; 27 were evaluable for DLT: six at 300 mg/m2, 11 at 350 mg/m2 (one DLT), and 10 at 400 mg/m2 (one DLT). The mean AUCs at 300 mg/m2, 350 mg/m2, and 400 mg/m2 were 2.20 μg h/mL, 2.52 μg h/mL, and 2.66 μg h/mL, respectively. The most common adverse event was diarrhea (93%; ≥grade 3: 11%). Seven patients stopped because of intolerance and eight because of insufficient response. Complete cytogenetic and major molecular response to bosutinib appeared comparable with other published phase I/II trials with second-generation TKIs in children. CONCLUSION: Bosutinib was safe and effective. The pediatric RP2D was 400 mg/m2 once daily (max 600 mg/d) with food in R/I patients and 300 mg/m2 once daily (max 500 mg/d) with food in ND patients, which achieved targeted exposures as per adult experience.
EVALuna2:550441